2011
DOI: 10.1102/1470-7330.2011.0015
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant treatment of colorectal liver metastases is associated with altered contrast enhancement on computed tomography

Abstract: Neoadjuvant systemic therapy may induce steatosis or sinusoid obstruction syndrome in the liver. The aim of this study was to investigate the influence of systemic therapy with irinotecan, oxaliplatin and cetuximab on conspicuity of liver metastases on computed tomography (CT). CT scans of 48 patients with initial unresectable colorectal liver metastases which were treated in a Europe-wide, opened, randomized phase II trial receiving oxaliplatin or irinotecan combined with folinic acid and cetuximab were analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…The imaging modalities used in these studies were mostly limited to contrast material-enhanced magnetic resonance (MR) imaging (15)(16)(17), which showed that SOS manifested as diffuse and heterogeneous signal intensity. However, Bethke et al reported that portal venous phase contrast-enhanced computed tomography (CT) demonstrated reduction of hepatic parenchymal attenuation following neoadjuvant chemotherapy, compared with baseline CT in the portal venous phase, and that SOS may be associated with this change (18). They indicated that SOS would have caused sinusoid congestion and therefore delays contrast agent inflow (18).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The imaging modalities used in these studies were mostly limited to contrast material-enhanced magnetic resonance (MR) imaging (15)(16)(17), which showed that SOS manifested as diffuse and heterogeneous signal intensity. However, Bethke et al reported that portal venous phase contrast-enhanced computed tomography (CT) demonstrated reduction of hepatic parenchymal attenuation following neoadjuvant chemotherapy, compared with baseline CT in the portal venous phase, and that SOS may be associated with this change (18). They indicated that SOS would have caused sinusoid congestion and therefore delays contrast agent inflow (18).…”
Section: Discussionmentioning
confidence: 95%
“…However, Bethke et al reported that portal venous phase contrast-enhanced computed tomography (CT) demonstrated reduction of hepatic parenchymal attenuation following neoadjuvant chemotherapy, compared with baseline CT in the portal venous phase, and that SOS may be associated with this change (18). They indicated that SOS would have caused sinusoid congestion and therefore delays contrast agent inflow (18). We also have experienced many patients with newly developed hepatic parenchymal heterogeneity on multi-detector row CT scans following OBC and have regarded this change in the hepatic parenchyma as finding associated with chemotherapy-induced SOS, because it resembled the findings of CT and MR imaging-detected SOS in previous literature (15)(16)(17)(18).…”
Section: Discussionmentioning
confidence: 95%
“…With a more homogeneous distribution of individuals, no statistical significance has been observed for HU min trend. Another study focusing on neoadjuvant treatment of colorectal liver metastases also found no differences in density before and after chemotherapy [37] . The reason why we did not observe any impact of the parameters analyzed on clinically relevant end points such as OS and TTP is probably a change in therapy respecting the results of the second CT scans.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is still controversial if the extent of necrosis in liver metastases in relation to the surrounding tumor tissue increases or decreases after the initiation of chemotherapy [39,40] . In addition, morphological changes to hepatic tissue caused by chemotherapeutic agents, such as steatosis or sinusoid obstruction, may lead to an underestimation of metastases [37,41] . Although baseline HU min was of statistical significance concerning OS, we cannot exclude that this is due to the small number of individuals in some of the subgroups analyzed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation